Return on Asset, Capital Intensity, Firm Size, dan Pengaruhnya Terhadap Agresivitas Pajak Pada Sektor Basic Materials Periode 2019-2023 - Anisa Nurmaulidya; Nanu Hasanuh (P3M Politeknik Negeri Bengkalis, 2025)
The existence of taxes in Indonesia has a significant impact on the economy because it is the largest contributor to the gonverment budget. However, in reality, there is still a lot of tax avoidance that has the potential to harm the country. As reported by News DTTC regarding a loss of IDR 65T due to tax avoidance and reported by Kompas regarding the decline in the sector's contribution to tax revenue. Therefore, this article aims to analyze the effect of return on assets, capital intensity, firm size on tax aggressiveness represented by the effective tax rate. The study was conducted in the basic materials sector listed on the Indonesian Stock Exchange and classified as an LQ45 company during the 2019–2023 period. From 96 populations, 6 company samples were obtained. The data was processed with SPSS version 26. Using the classical assumption test consisting of normality, multicollinearity, autocorrelation, and heteroscedasticity tests, as well as multiple linear regression to test the hypothesis. The results show that return on assets has a significant effect on the effective tax rate, while capital intensity and Firm Size have no effect on it. The results of ANOVA test indicate that regression model is significant, which means ROA, CI, and LnA collectively influence ETR.